Dynamics and control of distributed systems - Tzou, H. S. (Horn S.); Bergman, Lawrence A. (Cambridge : Cambridge University Press, 1998)
Distributed parameter systems encompass a broad range of engineering applications from stereo speakers to space structures. The dynamic behaviour of these systems is usually governed by one or more partial differential equations, which may accurately represent the physical system but are often difficult to solve exactly. Research in the dynamics and control of distributed parameter structural systems has grown dramatically in recent years, owing in part to the increasing complexity of these systems. Emerging technologies such as smart materials and mechatronics have contributed to growth in interest. The purpose of this book is to document progress in both theory and practical applications. Chapters discuss simulation, modelling, and analysis techniques used to investigate a variety of elastic, electromechanical and acoustic systems. With contributions by leading authorities, this book will serve as a resource for researchers and graduate students and also as a useful reference for practising engineers working in the area of dynamics and control of distributed systems.
1. On the Transient Response of Distributed Structures Interacting with Discrete Components / W.D. Zhu and C.D. Mote, Jr. -- 2. On the Problem of a Distributed Parameter System Carrying a Moving Oscillator / B. Yang, C.A. Tan and L.A. Bergman -- 3. Nonlinear Normal Modes and Wave Transmission in a Class of Periodic Continuous Systems / V.N. Pilipchuk and A.F. Vakakis -- 4. Dynamics and Control of Articulated Anisotropic Timoshenko Beams / A.V. Balakrishnan -- 5. Numerical Techniques for Simulation, Parameter Estimation, and Noise Control in Structural Acoustic Systems / H.T. Banks and R.C. Smith -- 6. Distributed Transfer Function Analysis of Stepped and Ring-stiffened Cylindrical Shells / B. Yang and J. Zhou.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Vibration -- Mathematical models; Distributed parameter systems; Structural control (Engineering)